PENGARUH WAKTU PEMBUSUKAN YUYU SAWAH (Parathelphusa convexa) TERHADAP KETERTARIKAN HAMA WALANG SANGIT (Leptocorisa oratorius) PADA TANAMAN PADI - Ariana, I Made Eka; Javandira, Cokorda; Sapanca, Putu Lasmi Yuliyanthi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
This study entitled The effect of time of decomposition of yuyu rice fields (Parathelphusa convexa) on the interest of pest (Leptocorisa oratorius) on rice plants. This research was conducted for two months, starting from November until December 2019. This study aimed to determine the effect of the time of yuyu rice field carcass decay on the interest of pest pest control. This study used a randomized block design (RBD) with eight treatments and one control that was repeated three times, using traps that were designed specifically and in each trap put in the form of bait yuyu carcasses. the results of research on the fifth treatment (yuyu carcasses of rice fields that were decomposed for five days) had the most attractive results of pest pest pest which is with an average number of horned puppet trap which was trapped at 13.33 tails.